Transport of pharmaceuticals and their metabolites between water and sediments as a further potential exposure for aquatic organisms - Koba, Olga; Grabicova, Katerina; Cerveny, Daniel; Turek, Jan; Kolarova, Jitka; Randak, Tomas; Zlabek, Vladimir; Grabic, Roman (Journal of hazardous materials, 2018)
Although pharmaceuticals are frequently studied contaminants, their fate in the environment is still not completely clear. During a one year study, a complex approach including water, sediment and fish sampling was used to describe the behaviour of pharmaceuticals and their metabolites (PTMs) in the environment. Eighteen pharmaceuticals and seven of their metabolites were determined in a pond used for the tertiary treatment of wastewater effluent. A liquid chromatography-tandem mass spectrometry method was applied to determine the PTMs concentrations in all matrices. Seasonal variations in concentrations were evaluated. The partitioning of contaminants between pond compartments was estimated by means of solid water distribution coefficients (Kd) and bioaccumulation factors (BAF) for the livers of fish. Kd values were almost stable throughout the year, which may be a sign of the continuous transport of PTMs between water and sediment under the experimental conditions. Almost all of the studied compounds, with exception of sertraline (BAF of 6200), were found to not be bioaccumulative in fish livers. The pond removal efficiency was calculated for all PTMs, and favourable conditions for natural pharmaceutical removal were proposed. Further aspects regarding fish pharmaceutical exposure need to be studied.
Keywords: Biological pond; Chromatography, Liquid; Fish; Pharmaceutical Preparations; geologické sedimenty; vodní organismy; Solid water distribution coefficient; voda; Bioaccumulation factor; odpadní voda; Waste Water; Drugs; chromatografie kapalinová; Water; ryby; Fishes; léčivé přípravky; Geologic Sediments; Animals; Aquatic Organisms; roční období; Seasons; zvířata; Fate; Wastewater